PENGARUH BIAYA OVERHEAD PABRIK TERHADAP PENJUALAN - Euis Hernawati (POLITEKNIK PIKSI GANESHA, 2022)
The purpose of this study was to know the influence this of factory overhead cost to sale at CV. Duta Setia Garment. The method used in conducting this research was deskriptive quantitative method with data collection technicques based on interview, observation and literature study. The collected data was then analyzed using statistical test of correlation coefficients and coefficients of determination. Based on the result of the study,it showed that result of correlation analysis the value of factory overhead cost to sale was 0,669 that value was positive. It could be interpreted in line with the criteria correlation was medium because it was within the interval (0,40 to 0,599). The result of the analysis of the influence of factory overhead cost determination to sale in the amount of 19,50% (the dependent variabel) and the remainder is 80,50% of other variables.